Tingkat Kepuasan Konsumen Abang Kumis Coffee Kecamatan Singkil Kota Manado - Rasubala, Satrio Kristian; Pangemanan, Paulus Adrian; Baroleh, Jenny (Sam Ratulangi University, 2023)
This study aims to measure the level of customer satisfaction at the Abang Mustache Coffee café, in terms of product, price, place, promotion and service aspects. This research was conducted in September - November 2022. The data collection method used in this study used primary and secondary data. Respondents in this study consisted of 89 people selected using accidental sampling technique. Data is measured with a Likert scale, then analyzed using the Consumer Satisfaction Index. The results showed that the level of customer satisfaction at the Abang Kumis Coffee café is classified as very satisfied with a consumer satisfaction index of 81.28%. More specifically for each aspect, the level of satisfaction with the product is 83%, price is 85.09%, promotion is 85.16%, service is 83.81% which is classified as very satisfied while 74.16% is only included in the satisfied category.